VISUAL REPRESENTATION ON CHILDREN BOOK BY ROALD DAHL’S CHARLIE AND THE CHOCOLATE FACTORY: SOCIAL SEMIOTIC STUDY - Widhianto, Anom; Kurniawan, Muhammad Hafiz (Universitas Putera Batam, 2023)
Visual image in the book is an important part of making a literary work especially in children picture book and the visual image were studied in social semiotic. This research aims to find the visual representation in children book Charlie and The Chocolate Factory written by Roald Dahl in 1964, as well as to identify the meaning by explaining social semiotic through visual representation in representational meaning, character manifestation, appearance and inter-circumstance by Painter. This study classified into qualitative research and types of data in this research classified into document of analyzing. While the steps collecting and analyzing data the researcher using social semiotic approach through multimodality by Bezemer and Jewitt: collecting and logging, viewing, sampling and transcribing the data. Then, for analyzed the data using visual representation (narrative representation, conceptual representation, and embedding) by Kress and Leeuwen also character manifestation, appearance, and inter-circumstance by Painter. This research used qualitative descriptive method in reporting the result of analysis in which description took the most important role in displaying the data analysis. The researcher found 43 of illustration images in the context of children book Charlie and The Chocolate Factory. The researchers found narrative representation (40), conceptual representation (3), embedding (images that contain narrative and conceptual representation) (4). Then, the researcher found appear (12), reappear (28), and 3 images are not counted because there is no character in the structure of character appearance. All of data or 43 images classified complete feature in the structure of character manifestation, and all of data classified into sustain degree in the structure of inter-circumstance. The result of this research is be able to explain the visual representation meaning, character manifestation, appearance, and inter-circumstance which found in children book Charlie and The Chocolate Factory.